Novel blood product transfusion regimen to prevent clotting and citrate accumulation during continuous renal replacement therapy with regional citrate anticoagulation in children - Sun, Yuelin; Li, Dong; Bai, Ke; Xu, Feng; Liu, Chengjun; Dang, Hongxing (Frontiers in Pediatrics, 2023)
Objective Introduce a novel protocol to prevent clotting and citrate accumulation (CA) from blood product transfusion (BPT) during continuous renal replacement therapy (CRRT) with regional citrate anticoagulation (RCA) in children. Methods We prospectively compared fresh frozen plasma (FFP) and platelet transfusions between the two BPT protocols, direct transfusion protocol (DTP) and partial replacement of citrate transfusion protocol (PRCTP), in terms of the risks of clotting, citric accumulation (CA), and hypocalcemia. For DTP, blood products were directly transfused without any adjustment to the original RCA-CRRT regimen. For PRCTP, the blood products were infused into the CRRT circulation near the sodium citrate infusion point, and the dosage of 4% sodium citrate was reduced depending on the dosage of sodium citrate in the blood products. Basic information and clinical data were recorded for all children. Heart rate, blood pressure, ionized calcium (iCa) and various pressure parameters were recorded before, during and after BPT, as well as coagulation indicators, electrolytes, and blood cell counts before and after BPT. Results Twenty-six children received 44 PRCTPs and 15 children received 20 DTPs. The two groups had similar in vitro ionized calcium (iCa) concentrations (PRCTP: 0.33 ± 0.06 mmol/L, DTP: 0.31 ± 0.04 mmol/L), total filter lifespan (PRCTP: 49.33 ± 18.58, DTP: 50.65 ± 13.57 h), and filter lifespan after BPT (PRCTP: 25.31 ± 13.87, DTP: 23.39 ± 11.34 h). There was no visible filter clotting during BPT in any of the two groups. The two groups had no significant differences in arterial pressure, venous pressure, and transmembrane pressure before, during, or after BPT. Neither treatment led to significant decreases in WBC, RBC, or hemoglobin. The platelet transfusion group and the FFP group each had no significant decrease in platelets, and no significant increases in PT, APTT, and D-dimer. The most clinically significant changes were in the DTP group, in which the ratio of total calcium to ionized calcium (T/iCa) increased from 2.06 ± 0.19 to 2.52 ± 0.35, the percentage of patients with T/iCa above 2.5 increased from 5.0% to 45%, and the level of in vivo iCa increased from 1.02 ± 0.11 to 1.06 ± 0.09 mmol/L (all p < 0.05). Changes in these three indicators were not significant in the PRCTP group. Conclusion Neither protocol was associated with filter clotting during RCA-CRRT. However, PRCTP was superior to DTP because it did not increase the risk of CA and hypocalcemia.